Characterization of Biomaterials with Rose Petal Properties by Adapting Hyperelastic Models - Muhammad Iman Sufi Suliman; Nur Shahira Mohd Arif; Abdul Wahab, Abdul Malek; Muhammad Ilham Khalit; Abdullah, Abdul Halim; Adull Manan, Nor Fazli (International Journal of Integrated Engineering, 2024)
The rose petals will be used together with other biomaterial compositions that would fit in artificial skin composition-based to improve the enhancement of healing agents. The objective of this project is to develop biomaterial with the enhancement of rose petals which acts as a healing agent for skin substitutes, and to characterize its mechanical properties that suit hyperelastic models. The methodology process involves mixing silicone rubber, gelatin, glycerin, distilled water, and rose petal powder to carry out the mechanical properties and hyperelastic behavior that could mimic the skin of mechanical properties. A double-boiling process was used and continuously stirred the mixtures up to 90°C before being poured into the 3D print mold. ASTM D412 is a uniaxial tensile test standard with a constant speed rate of 50 mm/min that was used in this study. The raw data from the computational Load-Extension was plotted on a graph of stress-strain and stress-stretch. The numerical approach of hyperelastic models such as Mooney-Rivlin and Yeoh are selected to analyze stress-stretch of biocomposite of skin substitute. The constant, C1, is in the range of 0.0344-0.0385 MPa, while C2 is in the negative range of 0.0365-0.0829 MPa, according to the Mooney-Rivlin model results. Meanwhile, for the Yeoh model, the constant, CP, is in the range of 0.00695-0.0122 MPa. The combination of silicone rubber, gelatin, glycerin, distilled water, and rose petal powder is homogeneous because lies within the skin’s mechanical properties range. This study has significantly contributed to a better understanding of the mechanical properties of biocomposite.